1994
DOI: 10.1159/000150396
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the Coding Potential and Expression of H-ras in Human Cytomegalovirus-Transformed Cells

Abstract: CMV-transformed cell lines demonstrated a greater level of H-ras RNA (7.5-to 9.5-fold) relative to the level for H-ras in parental cells. Nuclear run off assays showed that the RNA levels for the H-ras gene were regulated at the level of transcriptional initiation. The increased RNA levels for H-ras correlated with the level of p21rasVal-12 in transformed cells, while p21raíVal-12 was below the level of detection in nontransformed cells using Western blot analysis. In addition, an activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In a similar vein, Boldogh et al (47) have shown that three different cell lines transformed by HCMV infection harbor an activating mutation in both alleles in H-Ras. However, in both of these cases it is unclear whether the mutations in H-Ras or p53 are a direct result of the mutagenic activity of HCMV gene products.…”
Section: Discussionmentioning
confidence: 82%
“…In a similar vein, Boldogh et al (47) have shown that three different cell lines transformed by HCMV infection harbor an activating mutation in both alleles in H-Ras. However, in both of these cases it is unclear whether the mutations in H-Ras or p53 are a direct result of the mutagenic activity of HCMV gene products.…”
Section: Discussionmentioning
confidence: 82%
“…In the case of HCMV infection, a number of other mechanisms such as stimulation of growth factors or proto-oncogenes and inhibition of cellular apoptotic pathways may play a role in altering cell growth. Boldogh et al (11)(12)(13)(14)18) have demonstrated that HCMV infection activated a number of proto-oncogenes, such as c-myc, c-fos, and c-jun, and signaltransducing proteins such as H-ras. Jault et al (83) have shown that HCMV infection also resulted in the activation of a number of cell cycle-regulatory proteins such as p53, phosphorylated Rb, and cyclins.…”
Section: Resultsmentioning
confidence: 99%
“…The blotted RNA was analyzed using oligonucleotide probes to IFN-y (Clontech, Palo Alto, CA) or to a reference gene (G3PDH; Clontech). The oligonucleotides were labeled and the hybridizations were undertaken as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
“…(24). The abundance of PCR products bound to the membranes was analyzed by hybridization (25) to [32P]labeled oligonucleotide probes (specific activities were between 6.4 and 7.8 cpm/pmol) for target (IFN-y) and reference (G3PDH) genes (Clontech). The levels of hybridization were visualized by autoradiography.…”
Section: Methodsmentioning
confidence: 99%